2022
DOI: 10.1002/ptr.7425
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of functional foods against Parkinson's disease: A narrative review on pharmacology, phytochemistry, and molecular mechanisms

Abstract: In Persian Medicine (PM), PD (brain‐based tremor) is a known CNS disorder with several therapeutic and preventive options. In their medical textbooks and pharmacopeias, Persian great scientists such as Rhazes (854–925 AD), Avicenna (980–1037 AD), and Jorjani (1042–1136 AD), have discussed pharmacological and nutritional strategies for the prevention, slowing progression, and treatment of PD. In the present study, we surveyed plant‐ and animal‐based foods recommended by PM for the prevention and treatment of CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 197 publications
0
11
0
Order By: Relevance
“…According to the FDA of multiple countries, CA is proved as no safety concerns at doses of not exceeding daily acceptable consumption, whereas higher and nonnutritional intake of CA is prone to the appearance of genetic alteration and hepatotoxicity [ 15 ]. It is deciphered that CA administration in cellular and animal studies conducted at a specific period of time determines its absence of toxicity and carcinogenicity, the possible effects of this compound regarding long-term duration and other delivery routes are still vague [ 167 , 168 ]. The results of previous animal studies indicate that CA has a wide spectrum of efficacious dosage against CVDs, ranging from 5 mg/kg to 200 mg/kg.…”
Section: Potential Risks Of Camentioning
confidence: 99%
“…According to the FDA of multiple countries, CA is proved as no safety concerns at doses of not exceeding daily acceptable consumption, whereas higher and nonnutritional intake of CA is prone to the appearance of genetic alteration and hepatotoxicity [ 15 ]. It is deciphered that CA administration in cellular and animal studies conducted at a specific period of time determines its absence of toxicity and carcinogenicity, the possible effects of this compound regarding long-term duration and other delivery routes are still vague [ 167 , 168 ]. The results of previous animal studies indicate that CA has a wide spectrum of efficacious dosage against CVDs, ranging from 5 mg/kg to 200 mg/kg.…”
Section: Potential Risks Of Camentioning
confidence: 99%
“…In a study from 2015, a 6-month administration of 100 mg/day soy isoflavones did not prove effective on cognitive parameters in men and women over the age of 60 with AD [202]. Other studies have investigated the effect of isoflavones treatment on cognitive functions, displaying with controversial results [203].…”
Section: Isoflavones In Alzheimer's (Ad) and Parkinson's Diseases (Pd)mentioning
confidence: 99%
“…Autophagy modulators include natural compounds and synthesized pharmaceuticals that alter AMPK activity. The former includes resveratrol and caffeine [ 334 , 335 ], the latter include metformin [ 336 ], A769662 and GSK621 [ 337 ], Rosuvastatin [ 184 ], FCPR16 [ 338 ], and Temozolomide [ 339 ]. Of the natural compounds that act mainly on mTORC1, we note rapamycin and its analogs CCI-779 and AP23573 [ 340 , 341 ], Corynoxine [ 342 ], and Loganin [ 343 ].…”
Section: Treatment and Optimization Of The Condition Of Patients With Pdmentioning
confidence: 99%
“…In experiments predominantly in vitro and in animal models, it has been shown that they promote neuronal survival and neurite growth and facilitate functional recovery by invoking distinct mechanisms that are related to their roles as antioxidants, dopamine transporter inhibitors, monoamine oxidase inhibitors, free radical scavengers, chelators of harmful metal ions, modulating cell survival genes and signaling, anti-apoptosis activity, and even improving brain blood circulation. Garlic and allicin, cabbage and isothiocyanates, chickpea seed and its O-methylated isoflavones biochanin A and formononetin, cinnamon, and cinnamaldehyde, saffron and its crocin, crocetin, and safranal, black cumin and its thymoquinone, black pepper and piperine, pistachio and genistein and daidzein, and resveratrol are among the most effective dietary items against PD [ 334 ]. They act by attenuating neurotoxin-induced memory loss and behavioral impairment, oxidative stress, and dopaminergic cell death, thus alleviating PD progression.…”
Section: Treatment and Optimization Of The Condition Of Patients With Pdmentioning
confidence: 99%